2018
DOI: 10.1002/ccd.27523
|View full text |Cite
|
Sign up to set email alerts
|

Increased mortality in octogenarians treated for lifestyle limiting claudication

Abstract: Although endovascular techniques seem to dominate the care for octogenarians with LLC, the overall morbidity and mortality rates are significantly higher in this patient population. Other options such as medical management and/or supervised exercise therapy should be explored in this patient group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…6 Medical therapy and lifestyle modifications are usually considered the preferred therapeutic strategies for elderly as the rate of complications and risk of mortality is found to be higher in patients undergoing surgical interventions like that for lower limb claudication. 11 Multimorbidity, as found by our study and many other studies worldwide is an emerging health problem and extensive research is being carried to study the patterns of multi-morbidity. Our study found the co-occurrence of diseases like diabetes mellitus and hypertension, hypertension and cerebrovascular accidents, hypertension and chronic kidney disease, based on the pathological changes that one disease brings in the body aggravating the effect of or causing the other disease.…”
Section: Discussionsupporting
confidence: 62%
“…6 Medical therapy and lifestyle modifications are usually considered the preferred therapeutic strategies for elderly as the rate of complications and risk of mortality is found to be higher in patients undergoing surgical interventions like that for lower limb claudication. 11 Multimorbidity, as found by our study and many other studies worldwide is an emerging health problem and extensive research is being carried to study the patterns of multi-morbidity. Our study found the co-occurrence of diseases like diabetes mellitus and hypertension, hypertension and cerebrovascular accidents, hypertension and chronic kidney disease, based on the pathological changes that one disease brings in the body aggravating the effect of or causing the other disease.…”
Section: Discussionsupporting
confidence: 62%
“…In retrospective cohorts of patients with PAD, morbidity, functional status, prescription of GDMT, and overall mortality were significantly worse after revascularization procedures and major amputation in elderly patients when compared with younger patients with PAD. 14,15,20,21 Identification of these geriatric syndromes in older adults with PAD can be a catalyst for shared decision-making to evaluate the use of endovascular, surgical, or hybrid revascularization procedures to balance the risk of complications or loss of independence against the potential for improved QOL and palliation of symptoms with a limited life span.…”
Section: Special Considerations In Pad: Risk Amplifiers Health Dispar...mentioning
confidence: 99%